Synergistic Effect of Cation and Anion for Low-Temperature Aqueous Zinc-Ion Battery - Sun, Tianjiang; Zheng, Shibing; Du, Haihui; Tao, Zhanliang (Nano-Micro Letters, 2021)
Although aqueous zinc-ion batteries have gained great development due to their many merits, the frozen aqueous electrolyte hinders their practical application at low temperature conditions. Here, the synergistic effect of cation and anion to break the hydrogen-bonds network of original water molecules is demonstrated by multi-perspective characterization. Then, an aqueous-salt hydrates deep eutectic solvent of 3.5 M Mg(ClO4)2 + 1 M Zn(ClO4)2 is proposed and displays an ultralow freezing point of − 121 °C. A high ionic conductivity of 1.41 mS cm−1 and low viscosity of 22.9 mPa s at − 70 °C imply a fast ions transport behavior of this electrolyte. With the benefits of the low-temperature electrolyte, the fabricated Zn||Pyrene-4,5,9,10-tetraone (PTO) and Zn||Phenazine (PNZ) batteries exhibit satisfactory low-temperature performance. For example, Zn||PTO battery shows a high discharge capacity of 101.5 mAh g−1 at 0.5 C (200 mA g−1) and 71 mAh g−1 at 3 C (1.2 A g−1) when the temperature drops to − 70 °C. This work provides an unique view to design anti-freezing aqueous electrolyte. Highlights: 1 The ratio of hydrogen bonds in water molecules is significantly decreased by introducing oxygen-ligand Mg2+ and hydrogen-ligand ClO4−, resulting in an ultralow solidifying point of − 121 °C. 2 The excellent low-temperature physicochemical properties and good compatibility with Zn metal of 3.5 M (mol L−1) Mg(ClO4)2 + 1 M Zn(ClO4)2 electrolyte gives fabricated Zn||pyrene-4,5,9,10-tetraone (PTO) battery and Zn||Phenazine (PNZ) battery a satisfactory low temperature performance.